酶催化酯化法降低模型油中3-氯丙醇酯 和缩水甘油酯前体物质工艺研究 Reduction of 3-chloropropanol esters and glycidyl esters precursors in model oils by enzyme-catalyzed esterification - 冯兆寒，周燕霞，孙尚德 FENG Zhaohan, ZHOU Yanxia, SUN Shangde (Zhongguo youzhi)
旨在解决精炼过程中的高温条件易使油脂产生对人体有害的风险因子3-氯丙醇酯和缩水甘油酯问题，采用脂肪酶催化脂肪酸（油酸）与大豆模型油中的甘油一酯、甘油二酯进行酯化，以降低3-氯丙醇酯和缩水甘油酯的前体物质甘油一酯和甘油二酯的含量。采用单因素试验和响应面试验对酯化反应温度、脂肪酶添加量（以原料总质量计）、底物比（脂肪酸物质的量与将大豆模型油中甘油一酯和甘油二酯完全酯化为甘油三酯所需要脂肪酸总物质的量比）和反应时间等酯化反应条件进行优化。同时，使用酯化前后大豆模型油进行模拟脱臭反应，对比两种脱臭油中3-氯丙醇酯和缩水甘油酯的含量。结果表明：最优酯化反应条件为以Lipozyme RM IM为酯化用酶、脂肪酶添加量5.64%、反应温度78.82 ℃、底物比17.31∶ 1、反应时间29.05 h，在此条件下经过10倍放大试验，得到的酯化产物中甘油一酯含量为(0.29±0.01)%，甘油二酯含量为(2.39±0.03)%，甘油三酯含量为(97.32±0.04)%，甘油一酯和甘油二酯的含量分别较大豆模型油降低92.01%和75.05%。与未经过酯化反应的大豆模型油相比，经模拟脱臭后酯化大豆模型油中3-氯丙醇酯和缩水甘油酯含量分别降低58.06%和89.72%，分别为0.26 mg/kg和0.51 mg/kg，均符合欧盟标准要求。综上，通过酯化反应降低前体物质甘油一酯和甘油二酯的含量，可有效控制脱臭工序中3-氯丙醇酯尤其是缩水甘油酯的产生。 Aimed at solving the problem of high temperature conditions during the refining process that predispose oils to the production of 3-chloropropanol esters and glycidyl esters, which are risk factors that are harmful to human beings, enzyme-catalyzed esterification of fatty acid oleic acid with the monoglycerides and diglycerides in soybean model oils was conducted to reduce the contents of monoglycerides and diglycerides, precursors of 3-chloropropanol esters and glycidyl esters. The esterification reaction conditions were optimized using single factor experiment and response surface methodology, including reaction temperature, lipase dosage (based on the total mass of raw materials), substrate ratio (molar ratio of the amount of fatty acid substances to the total amount of fatty acid substances required for the complete esterification of monoglycerides and diglycerides to triglycerides in soybean model oils) and reaction time. At the same time,the deodorization reaction was simulated for soybean model oils before and after esterification, and the contents of 3-chloropropanol esters and glycidyl esters in the two deodorized oils were compared. The results showed that the optimal esterification reaction conditions were Lipozyme RM IM as the enzyme, lipase dosage 5.64%, reaction temperature 78.82 ℃, substrate ratio 17.31∶ 1, and reaction time 29.05 h. Under these conditions, the esterified products obtained after 10-fold scale-up test contained (0.29±0.01)% of monoglycerides, (2.39±0.03)% of diglycerides，and(97.32±004)% of triglycerides, and the contents of monoglycerides and diglycerides were 92.01% and 75.05% lower than that of the soybean model oils, respectively. Compared with the soybean model oils without esterification, the contents of 3-chloropropanol esters and glycidyl esters of esterified soybean model oils after simulated deodorization were reduced by 58.06% and 89.72%，which were 0.26 mg/kg and 0.51 mg/kg, respectively, and they were in line with the requirements of the EU standard. In conclusion, the production of 3-chloropropanol esters, especially glycidyl esters, can be effectively controlled by reducing the contents of monoglycerides and diglycerides through esterification reaction.